(untitled) (Bangladesh Journal of Agriculture, 2022)
Phytochemicals act against free radicals and are formed in human body continuously and damage body cells, causing many diseases like cellular damage, cancer, etc. Plant and their different parts are the main sources of phytochemicals. Litchi (Litchi chinensis Sonn.) is one of the most popular fruits of which only flesh is consumed by humans and the rest of the parts especially seeds are discarded. This study has been carried out to detect antioxidant potential in various extracts (aqueous and ethanol) of Bombay litchi variety seeds and to discover the contextual connection of phytochemicals as antioxidant activities. The collected seeds were washed, dried in sunlight, and finally ground to fine powder to a uniform particle size for extraction and isolation of phytochemicals. The qualitative and quantitative phytochemical analysis and antioxidant activities were determined using standard methods. Phytochemical screening reveals that most of the phytochemicals were extracted from litchi seed in ethanol. TPC and TFCs of ethanol extract were 19.86 and 20.60 mg/g, respectively. The antioxidant activity was estimated by DPPH assay method from litchi seed extracts, and IC50 of the seed phytochemicals and ascorbic acid was observed to be 274 and 240 μg/ml, respectively. On the other hand, free radical scavenging activities of seed phytochemicals were determined with ABTS assay; IC50 of seed phytochemicals and ascorbic acid was noted as 31 and 29 μg/ml, respectively. Results suggested that the litchi seed is one of the richest sources of phytochemicals that can be used as a source of bioactive compounds. It is concluded that bioactive litchi seed phytochemicals can be used as herbal medicine defense against aging, oxidative stress, cell damage as well as cancer. Bangladesh J. Agri. 2022, 47(1): 16-26